Peningkatan Kinerja Karyawan yang didasarkan pada Komitmen Organisasi, Beban Kerja dan Kepuasan Kerja pada PT. Bagoes Balindo Jaya Gianyar Bali - Tiksnayana Vipraprastha; Bagus Nyoman Kusuma Putra (Journal Research of Management, 2024)
The aim of this research is to find out whether organizational commitment, workload and job satisfaction influence the performance of PT Bagoes Balindo Jaya Gianyar Bali employees. Samples were collected using saturated sampling techniques, totaling 63 respondents. The data analysis technique used in this research is multiple linear regression analysis. The research results show that: (a) there is a significant and positive influence between organizational commitment on employee performance, (b) there is a significant and negative influence between workload on employee performance and (c) there is a significant and positive influence between job satisfaction on employee performance.